Comparative Analysis of Developed Expanding Urbanization and Floods Hit Erbil City Following Heavy Rainfall - Bahar Mohammed Ahmed; Shawmn Mudhafar Saleh; Shuokr Qarani Aziz; Sarwah Othman Ismael; Sarkawt Hamarahim Muhammad (Polytechnic Journal)
Climate change, urbanization, land use and land cover changes, and political and economic problems, caused increasing impervious layers and floods in Erbil Province in recent years. Due to economic growth and immigration from the middle and south of Iraq, the demand for residential areas has increased leading to more urban and impervious surface areas. The research aims to study the factors behind the increasing impervious areas and floods in Erbil City. Data were collected through several site visits and from related governmental sectors. Results illustrated that after 2017, urbanization noticeably increased. From 2017 to 2021, the construction zones and shrub areas were markedly increased. On the other hand, the agriculture area and green zone were significantly reduced. Additionally, the impervious layers increased and infiltration areas decreased only in four years. Moreover, some factors, such as geological, topographical, demographic, political, economic, and transportation, have affected the increase of urbanization and impervious areas, which increased surface runoff and floods in Erbil City.